2019
DOI: 10.3390/electronics8121522
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Retinal Fundus Image Classification Using Artificial Neural Networks (ANNs) and Reconfigurable Hardware (FPGA)

Abstract: Diabetic retinopathy (DR) and glaucoma are common eye diseases that affect a blood vessel in the retina and are two of the leading causes of vision loss around the world. Glaucoma is a common eye condition where the optic nerve that connects the eye to the brain becomes damaged, whereas DR is a complication of diabetes caused by high blood sugar levels damaging the back of the eye. In order to produce an accurate and early diagnosis, an extremely high number of retinal images needs to be processed. Given the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…After pruning these regions, we did not concede any accuracy drop. Adding to it, Ghani et al also demonstrated a region-of-interest-based image classification where they passed only the ROI data of an entire image for training a neural network and achieved 100% accuracy [ 32 ]. Therefore, it is an effective solution to prune redundant spatiotemporal information from images first and then apply the learning method to expedite the overall processing with optimal computation cost.…”
Section: Proposed Architecturementioning
confidence: 99%
“…After pruning these regions, we did not concede any accuracy drop. Adding to it, Ghani et al also demonstrated a region-of-interest-based image classification where they passed only the ROI data of an entire image for training a neural network and achieved 100% accuracy [ 32 ]. Therefore, it is an effective solution to prune redundant spatiotemporal information from images first and then apply the learning method to expedite the overall processing with optimal computation cost.…”
Section: Proposed Architecturementioning
confidence: 99%
“…Yet, there is a common problem with the above networks, i.e., to obtain accurate segmentation results, it often requires a lot of training time, and the segmentation efficiency of the network is very low. Arfan et al [26] proposed a method based on artificial neural networks and fully parallel field-programmable gate arrays (FPGAs). The hardware implementation proposed by this method can effectively improve the segmentation efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…Today, special attention in research is directed to the development of algorithms for processing fundus images [13][14][15][16][17]. Most importantly, the analysis of patient images using computer vision techniques in the treatment of diabetic retinopathy makes the process personalized and therefore more efficient and safer.…”
Section: Introductionmentioning
confidence: 99%